The Principle of Division of Obligations and Consumer Protection in Product Distribution Agreements: A Study of Business Law and Its Practice in Indonesia - Kurniawan, Muji Agung; Darmawan, Didit; Negara, Dharma Setiawan (Journal of Social Science Studies, 2024)
This study discusses the legal aspects of product distribution agreements in Indonesia, focusing on the division of responsibilities between manufacturers and distributors and the implementation of consumer protection. Through a normative legal approach, it explains how distribution agreements are positioned as unnamed agreements that remain subject to general principles of contract and are subject to trade regulations and consumer protection. Manufacturers are obliged to guarantee quality, accuracy of information, after-sales service, and administrative compliance. Distributors are responsible for proper distribution, maintaining product integrity, and providing services in accordance with the principal's standards. Consumer protection is implemented through the fulfilment of the rights to safety, information, freedom of choice, and the right to complain and seek redress in the event of loss due to defective products. This study emphasizes the importance of harmonizing contract clauses with applicable regulations and encourages the renewal of consumer protection strategies, both normatively and practically. Synergy between authorities, business actors, and consumers is the foundation of a fair and sustainable product distribution ecosystem.